Essays in economic and financial history - Tepper, A (2011)
Division One: “Malthus Gets Fat” (Two Chapters) Chapter One develops a simple dynamic model to examine the takeoff from a Malthusian economy to a modern growth regime. It finds that several factors, most notably the rate of technological progress and the economic structure, determine the fastest rate at which the population can grow without declining living standards; this is termed maximum sustainable population growth. It is only when this maximum sustainable rate exceeds the peak rate at which a society expands that takeoff can occur. I also investigate the effects of trade and international income transfers on the ability to sustain takeoff. It is also shown that present income growth is not necessarily indicative of the ability to sustain takeoff and that factors which increase current income growth may actually inhibit takeoff, and vice versa. Chapter Two applies the sustainable population growth framework to Britain during the Industrial Revolution. The model shows a dramatic increase in sustainable population growth at the time of the Industrial Revolution, well before the beginning of modern levels of income growth. The main contributions to the British breakout were technological improvements and structural change away from agricultural production. At least until the middle of the 19th Century, coal, capital and trade played a minor role. Division Two: “Leverage and Financial Market Instability” (Four Chapters) Chapter One develops a model of how leverage induces explosive behavior in financial markets. I show that when levered investors become too large relative to the market as a whole, the demand curve for securities can suddenly become upward-sloping as levered investors are exposed to forced liquidations. The size and leverage of all levered investors defines the minimum elasticity-adjusted market size for stability or MinEAMASS, which is the smallest elasticity-adjusted market size that can support the group of levered investors analyzed. This gives rise to a measure of instability that can predict when markets become vulnerable to a leverage-driven market liquidity crisis. Chapter Two iterates the model of Chapter One forward in time to generate an inflating bubble that suddenly bursts, reproducing many of Kindleberger's (1996) stylized facts about the dynamics of bubbles in a simple framework. Chapter Three applies my measure of instability in a historical investigation of the 1998 demise of hedge fund Long-Term Capital Management (LTCM). I find that a forced liquidation of LTCM threatened to destabilize some financial markets, particularly for bank funding and equity volatility. Chapter Four discusses how the model applied to the stock market crash of 1929. There the evidence suggests that a tightening of margin requirements in the first nine months of 1929 combined with price declines in September and early October caused enough investors to become constrained that the market was tipped into instability, triggering the sudden crash of October and November.